Marketing Efficiency of Ruminants in Mojosari Village, Kras District, Kediri Regency - Technacious Varid Sanjaya; Nur Solikin; Sapta Andaruisworo (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the marketing efficiency of ruminant livestock in Mojosari Village, Kras District, Kediri Regency. The methods used in this research include observation and active participation to collect data regarding the marketing structure and the buying and selling patterns of cattle and goats. The study was conducted in Mojosari Village, Kras District, Kediri Regency, by calculating livestock marketing costs. This research is expected to provide insights for farmers in improving marketing practices and strategic decision-making. The results of this study indicate that the marketing of ruminant livestock in Mojosari Village is already efficient.